Limited Variation in Bacterial Communities of Scaphoideus titanus (Hemiptera: Cicadellidae) Across European Populations and Different Life Stages - Juan Sebastian Enciso; Erika Corretto; Luigimaria Borruso; Hannes Schuler (Insects)
The Nearctic leafhopper Scaphoideus titanus (Hemiptera: Cicadellidae) is the primary vector of ‘Candidatus Phytoplasma vitis’, the causative agent of Flavescence doreé in Europe. Although microorganisms play an important role in the ecology and behavior of insects, knowledge about the interaction between S. titanus and microbes is limited. In this study, we employed an amplicon metabarcoding approach for profiling the V4 region of the 16S rRNA gene to characterize the bacterial communities of S. titanus across several populations from four European localities. Additionally, we investigated changes in bacterial communities between nymphal and adult stages. In total, we identified 7,472 amplicon sequence variants (ASVs) in adults from the European populations. At the genus level, ‘Candidatus Karelsulcia’ and ‘Candidatus Cardinium’ were the most abundant genera, with both being present in every individual. While we found significant changes in the microbial composition of S. titanus across different European populations, no significant differences were observed between nymphal and adult stages. Our study reveals new insights into the microbial composition of S. titanus and highlights the role of geography in influencing its bacterial community.